The Carcinogenic and Non-Carcinogenic Health Risks of Metal(oid)s Bioaccumulation in Leafy Vegetables: A Consumption Advisory - Alsafran, Mohammed; Usman, Kamal; Rizwan, Muhammad; Ahmed, Talaat; Al Jabri, Hareb (Frontiers in Environmental Science, 2021)
High levels of metal(oid)s in soil or food pose a severe health risk to humans. The potential toxicants find their way into the living systems via the food chain, following bioaccumulation in edible plants, including leafy vegetables grown in or irrigated with contaminated soil or water, respectively. The current study determines the levels of vanadium (V), chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), lead (Pb), and cadmium (Cd) in leafy vegetables (rocca, coriander, and parsley) grown in different open irrigated farms in Qatar and investigates their potential human health risks (carcinogenic and noncarcinogenic). The mean concentrations of V, Cr, Ni, Cu, As, Cd, and Pb in rocca are 17.09, 6.41, 1.70, 13.04, 14.72, 0.90, and 6.36 mg/kg, respectively; in coriander are 15.91, 6.03, 1.38, 15.30, 16.86, 0.43, and 5.00 mg/kg, respectively; and in parsley are 16.25, 6.26, 2.19, 17.97, 16.60, 0.51, and 5.46 mg/kg, respectively. The mean levels of V, Cr, As, Cd, and Pb were observed to be higher than the recommended World Health Organization (WHO)/Food and Agriculture Organization (FAO) values. The target hazard quotient (THQ) values of Cu and As were found to be greater than 1 for the adult population. For the two elements (i.e., Cu and As), the THQ varied from 1.03 to 1.42 and 1.17 to 1.44 in men. In women, the values ranged from 1.20 to 1.65 and 1.35 to 1.55, for Cu and As, respectively. The hazard index (HI) of rocca, coriander, and parsley was 3.99, 4.10, and 4.43, respectively, in men, 4.64, 4.76, and 5.14, respectively, among women. The carcinogenic risk (CR) of Cr, Ni, and As ranged from 7.16 × 10−4 to 7.61 × 10−4, 5.57 × 10−4 to 8.85 × 10−4, and 5.24 × 10−3 to 6.01 × 10−3, respectively, in men. In women, it ranged from 8.31 × 10−4 to 8.83 × 10−4, 6.47 × 10−4 to 1.03 × 10−3, and 6.09 × 10−3 to 6.97 × 10−3, respectively, in all vegetables. In crux, the consumption of rocca, coriander, and parsley grown in selected farms in Qatar poses a major health risk (both noncarcinogenic and carcinogenic) to the consumer. As a result, we recommend that vegetables grown in the studied areas be closely monitored to protect consumer health.